Peran Remaja Masjid Dalam Memakmurkan Masjid (Studi Kasus Manajemen Masjid Desa Kelinjau Ulu) - Muhammad Al Faizal; Mohammad Salehudin (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The purpose of this study was to determine the role of youth at the Jami'ul Hijrah Mosque in Prospering the Mosque, to describe the role of youth at the mosque in prospering the mosque (a case study of Jami'ul Mosque management). The role of mosque youth is very important in carrying out mosque management, but there are still some teenagers who are involved only playing a role in joint recitation activities, commemoration of Islamic holidays, routine vows or prayers, tambourine training, community service, and social service. This research is a field research (Field Research), using a qualitative descriptive method, namely a method that describes events in accordance with the actual situation. The results of the study found that they were quite good at carrying out program activities, and youth played an active role in the activities carried out, both activities in the mosque environment, and also had concern for the environment outside the mosque. So with teenagers playing a role in these activity programs can form a religious character. The role of mosque youth in the prosperity of the Jami'ul Hijrah mosque is quite good in terms of the involvement of youth in the management of the activities carried out, although it needs to be strengthened in mosque management which involves mosque youth in achieving predetermined work programs, even to prosper the mosque. Keyword : the role of youth, prospering the mosque, mosque management ABSTRAK Tujuan penelitian ini untuk mengetahui peran remaja Masjid Jami’ul Hijrah dalam Memakmurkan Masjid, untuk mendeskripsikan peran remaja masjid dalam memakmurkan masjid (studi kasus manajemen Masjid Jami’ul). Peranan remaja masjid sangat penting dalam menjalankan manajemen masjid, namun masih terdapat sebagain remaja yang terlibat hanya berperan dalam kegiatan mengaji bersama, peringatan hari besar Islam, rutinan berjanjen atau sholawat, latihan rebana, ikut kerja bakti, dan bakti social. Penelitian ini adalah penelitian lapangan (Field Research), dengan menggunakan metode deskriptif kualitatif yaitu metode yang menggambarkan kejadian sesuai dengan keadaan yang sebenarnya. Hasil penelitian ditemukan bahwa cukup baik dalam melakukan program kegiatan, dan remaja cukup berperan aktif dalam kegiatan yang dilakukan tersebut baik itu kegiatan di lingkungan masjid, dan juga memiliki kepedulian terhadap lingkungan di luar masjid. Jadi dengan remaja berperan dalam program kegiatan tersebut dapat membentuk karakter yang religius. Peran remaja masjid dalam memakmurkan masjid Jami’ul Hijrah cukup baik dalam arti keterlibatan remaja dalam manajemen kegiatan yang di lakukan, walaupun perlu diperkuat lagi pada manajemen masjid yang melibatkan remaja masjid dalam mencapai program kerja yang telah ditetapkan, bahkan untuk memakmurkan masjid. Kata Kunci : Peran Remaja, Manajemen Masjid, Memakmurkan Masjid